2010
DOI: 10.1186/1756-9966-29-29
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 regulates breast cancer invasion partly by targeting tissue inhibitor of metalloproteinase 3 expression

Abstract: BackgroundMicroRNAs are non-coding RNA molecules that posttranscriptionally regulate expression of target genes and have been implicated in the progress of cancer proliferation, differentiation and apoptosis. The aim of this study was to determine whether microRNA-21 (miR-21), a specific microRNA implicated in multiple aspects of carcinogenesis, impacts breast cancer invasion by regulating the tissue inhibitor of metalloproteinase 3 (TIMP3) gene.MethodsmiR-21 expression was investigated in 32 matched breast ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
128
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(137 citation statements)
references
References 27 publications
7
128
1
1
Order By: Relevance
“…Previous studies using clinical specimens and in vitro and in vivo models have identified a limited number of miRNAs that promote metastasis, including miR-200, miR-10b and miR-21 (30)(31)(32)(33). The present study revealed that miR-520e is associated with metastasis; upregulation of miR-520e may facilitate the metastasis of breast cancer cells and therefore the progression of breast cancer.…”
mentioning
confidence: 49%
“…Previous studies using clinical specimens and in vitro and in vivo models have identified a limited number of miRNAs that promote metastasis, including miR-200, miR-10b and miR-21 (30)(31)(32)(33). The present study revealed that miR-520e is associated with metastasis; upregulation of miR-520e may facilitate the metastasis of breast cancer cells and therefore the progression of breast cancer.…”
mentioning
confidence: 49%
“…It was recently demonstrated that microRNAs can promote tumor invasion and metastasis in breast cancer, suggesting that the dysregulation of specific miRNAs can provide a selective advantage in breast cancer metastasis. Various miRNAs serve as metastasis activators [miR-10b (33), miR-21 (34,35), miR-9 (36), miR-373 and miR-520c (37)] and are able to initiate invasion and metastasis in breast cancer. Some miRNAs serve as metastasis suppressors [miR-3 (38), miR-200 family (39,40), miR-335 and miR-126 (41)] and are able to inhibit invasion and metastasis in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we studied the expression of: (a) miR-21, which affects tumor invasion and inhibits tumor cell colonization (17)(18)(19)(20); (b) miR-205, which is involved in angiogenesis and is downregulated in epithelial-mesenchymal transitions (21 ); (c) miR-10b, which positively regulates cell migration and invasion (13 ); (d) miR-335, which modifies tumor microenvironment (12 ); (e) let-7a, which inhibits the proliferation and self-renewal of breast cancer stem cells (22 ); and (f) miR-210, which has been shown to be inversely associated with cancer aggressiveness and metastatic potential (23 ). We explored the relationships of the expression profiles for these miRNAs with clinical outcomes in FFPE samples from breast cancer patients, focusing in particular on ER and PR expression, HER2, and lymph node status.…”
mentioning
confidence: 99%